Effect of ground corn fractionation on flowability - Kalivoda, J. R.; Jones, Cassandra K.; Stark, Charles R. (My University, 2016)
Particle size reduction is an important component of feed manufacturing that impacts pellet quality and animal feed efficiency. However, reducing particle size too fine often results in reduced flowability of the ground corn and finished feed, which creates potential handling and storage concerns at the feed mill and farm. The objective of this experiment was to determine how fractionation affected flowability of ground corn. Whole corn was received from a single source and ground to achieve 3 target particle sizes, 400, 500, and 600 µm, with actual results of 469, 560, and 614 µm. Each target particle size was fractionated into 3 fractions: coarse ( > 630 µm), medium ( < 630 µm and > 282 µm), and fine ( < 282 µm) particles using a vibratory separator (model LS18SP3, SWECO, Florence, KY). Within each particle size, the percentage of ground corn as each fraction included: 400 µm: 57.5, 32.3, and 4.6% for coarse, medium, and fine, respectively; 500 µm: 64.4, 30.1, and 1.80% for coarse, medium, and fine, respectively; and 600 µm: 71.2, 23.2, and 0.90% for coarse, medium, and fine, respectively. When the target particle sizes were fractionated, their particle sizes were: 400 µm: 744, 269, and 94 µm for coarse, medium, and fine, respectively; 500 µm: 815, 253, and 96 µm for coarse, medium, and fine, respectively; and 600 µm: 898, 220, and 99 µm for coarse, medium, and fine, respectively. Fractionated samples were analyzed for multiple flowability characteristics, including: angle of repose, critical orifice diameter, composite flow index (CFI), density, and compressibility. Treatments were arranged in a nested model with 3 replicates per treatment. Data were analyzed using the GLIMMIX procedure of SAS. When particle size was analyzed as a main effect, density affected flowability (P = 0.014) with the 400 µm having the lowest density. However, when fraction was nested within particle size, it impacted (P < 0.001) all measures of flowability, with the fine fraction ( < 282 µm) of the 400 µm corn having the poorest flowability. In conclusion, reducing particle size resulted in the ground corn having poorer flowability characteristics, caused predominantly by particles that passed through 282 µm. Based on this data, producers may potentially grind corn to a lower particle size while maintaining flowability if fine particles ( < 282 µm) are removed.
Citation: Kalivoda, J. R., Jones, C. K., & Stark, C. R. (2016). Effect of ground corn fractionation on flowability. Journal of Animal Science, 94, 78-78. doi:10.2527/msasas2016-167
Keywords: Corn; Flowability; Particle Size Analysis; Agriculture